Bottom-Up versus Top-Down Induction of Sleep by Zolpidem Acting on Histaminergic and Neocortex Neurons - Uygun, David S. (J Neurosci, 2016)
Zolpidem, a GABA(A) receptor-positive modulator, is the gold-standard drug for treating insomnia. Zolpidem prolongs IPSCs to decrease sleep latency and increase sleep time, effects that depend on α2 and/or α3 subunit-containing receptors. Compared with natural NREM sleep, zolpidem also decreases the EEG power, an effect that depends on α1 subunit-containing receptors, and which may make zolpidem-induced sleep less optimal. In this paper, we investigate whether zolpidem needs to potentiate only particular GABAergic pathways to induce sleep without reducing EEG power. Mice with a knock-in F77I mutation in the GABA(A) receptor γ2 subunit gene are zolpidem-insensitive. Using these mice, GABA(A) receptors in the frontal motor neocortex and hypothalamic (tuberomammillary nucleus) histaminergic-neurons of γ2I77 mice were made selectively sensitive to zolpidem by genetically swapping the γ2I77 subunits with γ2F77 subunits. When histamine neurons were made selectively zolpidem-sensitive, systemic administration of zolpidem shortened sleep latency and increased sleep time. But in contrast to the effect of zolpidem on wild-type mice, the power in the EEG spectra of NREM sleep was not decreased, suggesting that these EEG power-reducing effects of zolpidem do not depend on reduced histamine release. Selective potentiation of GABA(A) receptors in the frontal cortex by systemic zolpidem administration also reduced sleep latency, but less so than for histamine neurons. These results could help with the design of new sedatives that induce a more natural sleep. SIGNIFICANCE STATEMENT Many people who find it hard to get to sleep take sedatives. Zolpidem (Ambien) is the most widely prescribed “sleeping pill.” It makes the inhibitory neurotransmitter GABA work better at its receptors throughout the brain. The sleep induced by zolpidem does not resemble natural sleep because it produces a lower power in the brain waves that occur while we are sleeping. We show using mouse genetics that zolpidem only needs to work on specific parts and cell types of the brain, including histamine neurons in the hypothalamus, to induce sleep but without reducing the power of the sleep. This knowledge could help in the design of sleeping pills that induce a more natural sleep.